Key process to use information system in Bangladesh hospitality industry - Rifat, A.K.M. Azimul Haque; Khan, Ahnaf Rahman; Fairoz, Faiza; Tanzim, Sarah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.